PENINGKATAN HASIL BELAJAR GERAK NON LOKOMOTOR MELALUI METODE DRILL DIKELAS IV SDN 13 TANJUNG BONAI KEC.LINTAU BUO UTARA - ERDAWATI ERDAWATI (STKIP Pesisir Selatan, 2020)
Based on the learning outcomes obtained by students in Class IV SDN 13 Tanjung Bonai in PJOK learning it was found that the learning outcomes of students in PJOK learning were still very low and many were under the KKM. The purpose of this study was to describe and obtain information about efforts to improve student learning outcomes Non locomotor Motion through the application of learning methods through the application of the Drill Method in Class IV SDN 13 Tanjung Bonai, Sawahlunto City. This research is a classroom action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 10 students of Class IV SDN 13 Tanjung Bonai. Research data were collected using tests. Data were analyzed using percentages. Based on the results of research and discussion, it can be concluded that the Drill Method can improve student learning outcomes in learning PJOK at SDN 13 Tanjung Bonai. Student learning outcomes from cycle I to cycle II have increased. Student learning outcomes in the first cycle was 68.67 (enough) increased to 75.59 (good) with an increase of 6.92.